2008
DOI: 10.1111/j.1748-0159.2008.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective nutrition labeling of restaurant menu and pricing of healthy menu

Abstract: Providing nutritional information on restaurant menus may help customers make healthier eating choices. This paper presents the results of a two‐phase study designed to identify (i) the most preferred amount of nutritional information for a menu, (ii) whether presentation of nutritional information influenced healthier choices, and (iii) whether people are willing to pay more for food choices they perceive to be healthier. We found that participants’ attitudes toward the amount of nutritional information and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
103
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 11 publications
(20 reference statements)
7
103
0
2
Order By: Relevance
“…Instead, participants wanted information about calories, total fat, saturated fat, sugar, and salt in 1 simple, easy-to-use format. This supports the work of Hwang and Lorenzen, 38 who found that multiple types of nutrition information were more effective and credible than only 1 type. Nonetheless, attempts to satisfy all information needs in a particular label are likely to result in label overload.…”
Section: Discussionsupporting
confidence: 89%
“…Instead, participants wanted information about calories, total fat, saturated fat, sugar, and salt in 1 simple, easy-to-use format. This supports the work of Hwang and Lorenzen, 38 who found that multiple types of nutrition information were more effective and credible than only 1 type. Nonetheless, attempts to satisfy all information needs in a particular label are likely to result in label overload.…”
Section: Discussionsupporting
confidence: 89%
“…In support of our study, other investigators have reported similar findings backing menu labeling [22][23][24]27,[33][34][35]; one of those studies reported findings similar to those in this study with 90% of the respondents reporting they would use nutrition information if it was available on restaurant menus [33].…”
Section: Discussionsupporting
confidence: 82%
“…These have closely looked into the impact of nutritional (see, for instance, Hwang and Lorenzen 2008;Josiam and Foster 2009;Thomas and Mills 2006) and calorific (see Kiszko et al 2014 for an up-to-date, comprehensive literature review) menu labelling. They have also investigated the role of displaying food origin (provenance), production methods and allergen information on the menu (see, for instance, Dupuis et al 2016;Hartwell and Edwards 2009) More research on menu (re-)design and its role in consumer food choice in restaurants is also required because the scope of analysis conducted in peer-reviewed literature to-date has been limited.…”
Section: 2the Role Of Menu Designmentioning
confidence: 99%